Device closure of ventricular septal defect: Initial experience in Nepal - Adhikari, Chandra Mani; Shrestha, Manish; Shah, Subash Chandra; Bogati, Amrit; Dhungel, Sachin; Acharya, Kiran Prasad; Sharma, Poonam; Aryal, Shilpa; Shakya, Urmila (Asian Journal of Medical Sciences, 2019)
Background: Device closure is an attractive alternative in the management of Ventricular Septal defect (VSD). Aims and Objective: The aim of the study was to access the safety and early outcome of VSD device closure at Shahid Gangalal National Heart Centre, Nepal. Materials and Methods: The study was single center, retrospective study. All the VSD cases who were attempted for VSD device closure during December 2016 to February 2019 were included. Catheterization laboratory records for VSD type and size, Device type and size were retrospectively reviewed. Hospital records were reviewed for in-hospital complications. Results: Sixty-one VSD cases were attempted for device closure. VSD was successfully closed in 55 (90.1%) patients. The mean age of the patient was 11.1 years. Twenty-nine (52.7%) were female and 26 (47.3%) were male. Perimembranous VSD in 49 (89 %) and muscular VSD in 6 (11 %) patients. The size of VSD ranged between 2 and 12mm (Mean 5.4mm). The VSD was closed with Amplatzer duct occluder I, Amplatzer duct occluder II, Amplatzer muscular VSD occluder and Memopart PDA device in 24 (43.7%), 26 (47.3%), 4 (7.2 %) and one patient (1.8%) patients respectively. The postoperative complications were insignicant residual leak across device in 2 (3.6%) patients, mild pericardial effusion in one (1.8%) patient. None of the patient had new onset tricuspid regurgitation, aortic regurgitation and complete heart block. One patient developed Right bundle branch block, one developed Left bundle branch block, one developed Junctional rhythm. There was no mortality. Conclusion: VSD device closure can be safe and effective if patients are selected properly.